Upaya Kepolisian dalam Menanggulangi Penambangan Emas Tanpa Izin (Peti) di Kabupaten Katingan - Jelita Anggeli Magdalena (Jurnal Hukum Lex Generalis, 2026)
Unlicensed Gold Mining (PETI) is still a legal and environmental problem in Katingan Regency. This study aims to analyze the efforts of the Katingan Resort Police in overcoming PETI and the obstacles faced. The method used is empirical juridical with a qualitative descriptive approach through interviews, observations and documentation. The results of the study show that the police make preventive efforts through counseling, appeals and patrols, as well as repressive efforts through investigations, arrests and seizures of mining equipment. However, these efforts have not been optimal due to low public legal awareness, economic factors, geographical conditions and limited facilities. It is recommended to increase integrated patrols, take action against PEPE financiers and provide alternative livelihoods for the community. This research is expected to serve as valuable input for law enforcement agencies and local governments in formulating more effective policies to combat illegal gold mining sustainably.